Redefining the bottom of the pyramid from a marketing perspective. (September 2017) - Yurdakul, Dicle; Atik, Deniz; Dholakia, Nikhilesh
Marketing literature has remained mostly silent on the issue of conceptualization of poverty, relying instead on the available definitions of the bottom-of-the-pyramid (BOP) "poor" from economics and sociology. Consequently, in marketing theory, the analytic bases and the practical implications of poverty-centered discourses sometimes remain ambiguous. This study provides a broader, culture-linked conceptualization of poverty and BOP from a consumer research perspective, initiating a dialogue on bottom-up approaches to understanding what poverty means through the lenses of the poor. Via qualitative methods such as semistructured individual in-depth interviews, observations, and fieldnotes, deeper insights were sought on how poverty can be defined from the perspectives of the poor. Transcending the economic-only approach, this study contributes to the literature by extending the contours of "felt poverty" and of the "poverty line" beyond the biogenic and stark utilitarian needs and incorporates the sociocultural dimensions of consumption. Our contribution comes from including the effects of the global consumer culture as a major source of social deprivation. Furthermore—while supporting the positions that the definitions of BOP are relative to contexts, cultures, and times—we also situate the discussion of BOP within the broader discourse on globalization of markets and consumption practices.